Next-generation in vivo optical imaging with short-wave infrared quantum dots - Bruns, Oliver Thomas; Riedemann, Lars (Nature biomedical engineering, 2017)
For in vivo imaging, the short-wavelength infrared region (SWIR; 1,000-2,000 nm) provides several advantages over the visible and near-infrared regions: general lack of autofluorescence, low light absorption by blood and tissue, and reduced scattering. However, the lack of versatile and functional SWIR emitters has prevented the general adoption of SWIR imaging by the biomedical research community. Here, we introduce a class of high-quality SWIR-emissive indium-arsenide-based quantum dots that are readily modifiable for various functional imaging applications, and that exhibit narrow and size-tunable emission and a dramatically higher emission quantum yield than previously described SWIR probes. To demonstrate the unprecedented combination of deep penetration, high spatial resolution, multicolour imaging and fast acquisition speed afforded by the SWIR quantum dots, we quantified, in mice, the metabolic turnover rates of lipoproteins in several organs simultaneously and in real time as well as heartbeat and breathing rates in awake and unrestrained animals, and generated detailed three-dimensional quantitative flow maps of the mouse brain vasculature.
Gesehen am 05.09.2018